2003
DOI: 10.1038/sj.gt.3301882
|View full text |Cite
|
Sign up to set email alerts
|

Transfection of NFκB-decoy oligodeoxynucleotides using efficient ultrasound-mediated gene transfer into donor kidneys prolonged survival of rat renal allografts

Abstract: Nuclear factor kB (NFkB) plays a pivotal role in the coordinated transactivation of a series of genes of cytokines and adhesion molecules that are highly involved in the onset of acute rejection in organ transplantation. We previously developed decoy cis-elements oligo deoxyribonucleic acid against NFkB (NFkB-decoy) that effectively inhibited the activation of major inflammatory mediators in vitro and in vivo. Accordingly, we hypothesized that transfection of NFkB-decoy into the donor kidney would prevent acut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(35 citation statements)
references
References 43 publications
(56 reference statements)
0
35
0
Order By: Relevance
“…Most in vivo studies have concentrated on organs and tissues that are readily imaged by diagnostic ultrasound machines, including skeletal muscle, heart and kidneys. 35,36,[48][49][50][51][52][53][54][55][56][57][58][59][60][61][62] Table 1 summarizes the results of some recent studies in these tissues using reporter genes, 35,36,[48][49][50][51][52][53][54]58,60,61 and broadly similar data have begun to emerge from studies in the vascular, 4,63,64 neurology 65-67 and oncology 18,37,68 fields, the pancreas 69 and in hematology. 70 On first inspection the relatively modest enhancements in plasmid-mediated transfection after USE in vivo may appear disappointing compared with the results obtained in vitro.…”
Section: Multiple Biophysical Effects Of Ultrasound May Contribute Tomentioning
confidence: 76%
“…Most in vivo studies have concentrated on organs and tissues that are readily imaged by diagnostic ultrasound machines, including skeletal muscle, heart and kidneys. 35,36,[48][49][50][51][52][53][54][55][56][57][58][59][60][61][62] Table 1 summarizes the results of some recent studies in these tissues using reporter genes, 35,36,[48][49][50][51][52][53][54]58,60,61 and broadly similar data have begun to emerge from studies in the vascular, 4,63,64 neurology 65-67 and oncology 18,37,68 fields, the pancreas 69 and in hematology. 70 On first inspection the relatively modest enhancements in plasmid-mediated transfection after USE in vivo may appear disappointing compared with the results obtained in vitro.…”
Section: Multiple Biophysical Effects Of Ultrasound May Contribute Tomentioning
confidence: 76%
“…Although there are many reports on sonoporation [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38], each experimental setting differs from one another and the reported sonoporation efficiency, which is one of the most significant information in sonoporation, varies. In order to understand the effect of the experimental settings themselves on sonoporation experiments, we first investigated the impact of the conditions of the cultured cells on sonoporation efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…(Current address: Department of Neurosurgery, Osaka University Medical School, 2-2 Yamadaoka, Suita, Oaska, 565-0871, Japan. Phone: +81-6-6879-3652: FAX: +81-6-6879-3659; e-mail : m-kinoshita@nsurg.med.osaka-u.ac.jp) hyperthermia, such as coagulation of tissues [1][2][3][4][5][6][7][8][9][10][11][12], mechnical tissue destruction [13,14], disruption of tight junctions of the vasculature for enhanced local drug delivery [15][16][17][18][19][20], and sonoporation, a transient enhanced permeability of the cell membrane caused by the combination of ultrasound and microbubbles [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38]. As all of these bio-effects can be created non-invasively in vivo, ultrasound is gathering a great attention as a next generation surgical or drug delivery system.…”
Section: Introductionmentioning
confidence: 99%
“…It has been well known that the transcriptional factor nuclear factor-kappa B (NF-κB) is mainly responsible for the regulation of these gene expressions (40). We and others have demonstrated that the suppression of NF-κB could become a novel therapeutic strategy for ischemia/ reperfusion-induced tissue damage (41,42). There is accumulating evidence that PBE has an inhibitory effect on NF-κB activation in macrophages and vascular endothelial cells (43,44).…”
Section: Renoprotective Effects Of Flavangenol In Ischemic Acute Kidnmentioning
confidence: 99%